2007
DOI: 10.1227/01.neu.0000285347.50028.b9
|View full text |Cite
|
Sign up to set email alerts
|

Exhaustive, ONE-YEAR FOLLOW-UP OF SUBTHALAMIC NUCLEUS DEEP BRAIN STIMULATION IN A LARGE, SINGLE-CENTER COHORT OF PARKINSONIAN PATIENTS

Abstract: The efficacy and safety of STN-DBS in our center's large cohort of Parkinsonian patients are generally similar to the results obtained by other groups, albeit at the lower limit of the range of reported values. In contrast to efficacy, the occurrence of adverse events cannot be predicted. Younger patients with Parkinson's disease (i.e., those younger than 60 yr) often show an excellent response to levodopa. However, in view of our data on overall patient satisfaction and the occurrence of adverse events, we su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
37
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(46 citation statements)
references
References 46 publications
9
37
0
Order By: Relevance
“…In a recent study, compared with baseline, the patients' scores at five years for motor function while off medication improved by 54% (p < 0.001) [30]. Tir et al reported a decrease by 43% in UPDRS-III scores 12 months after surgery [31]. Our results are in line with the literature.…”
Section: Discussionsupporting
confidence: 90%
“…In a recent study, compared with baseline, the patients' scores at five years for motor function while off medication improved by 54% (p < 0.001) [30]. Tir et al reported a decrease by 43% in UPDRS-III scores 12 months after surgery [31]. Our results are in line with the literature.…”
Section: Discussionsupporting
confidence: 90%
“…A similar lack of satisfaction has also been reported after DBS in patients with Parkinson's disease despite clinical improvement [Tir et al, 2007]. Not only patients' expectations are at the base of their satisfaction, but the caregivers' opinion may influence the judgment of the stimulation effect in the patients as well.…”
Section: Patients' Expectations Versus Realistic Outcomessupporting
confidence: 52%
“…Even when present, the impact of changes in verbal fluency on the quality of life appears to be relatively small (Alegret et al, 2004;Morrison et al, 2004;Montel and Bungener, 2009;Zahodne et al, 2009). Although almost half patients with DBS experience variable degrees of cognitive changes (Higginson et al, 2009), these deficits become 'relevant' in less than 10% treated patients (Castelli et al, 2006;Tir et al, 2007). However, because DBS is now widely used, even for patients with early PD in some centers, these adverse effects remain a major concern.…”
Section: Non-motor Side Effects Of Stn and Gpi-dbsmentioning
confidence: 99%
“…Although the underlying substrate of these side effects remains to be characterized, it has been suggested that they may be induced by stimulation in non-motor areas of STN or GPi, inadvertent involvement of limbic structures outside of the target regions (Bejjani et al, 1999;Krack and Vercueil, 2001;Kulisevsky et al, 2002;Romito et al, 2002;Herzog et al, 2003a;Okun et al, 2003;Stefurak et al, 2003), and preexisting psychiatric conditions (Lilleeng and Dietrichs, 2008). Although significant unpleasant mood side effects following STN or GPi DBS are relatively rare (Funkiewiez et al, 2004;Castelli et al, 2006;Tir et al, 2007), their occurrence significantly disrupts patients' quality of life.…”
Section: Non-motor Side Effects Of Stn and Gpi-dbsmentioning
confidence: 99%